2012
DOI: 10.1007/s00128-012-0538-6
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Biomass and Carbon Mineralization in Agricultural Soils as Affected by Pesticide Addition

Abstract: A laboratory study was conducted with four pesticides, viz. a fungicide (carbendazim), two insecticides (chlorpyrifos and cartap hydrochloride) and an herbicide (pretilachlor) applied to a sandy clay loam soil at a field rate to determine their effect on microbial biomass carbon (MBC) and carbon mineralization (C(min)). The MBC content of soil increased with time up to 30 days in cartap hydrochloride as well as chlorpyrifos treated soil. Thereafter, it decreased and reached close to the initial level by 90th d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Many researchers have noted an increase in the number of microorganisms under the influence of herbicides. Moreover, according to the literature a large number of bacteria, especially from Pseudomonas genus have the ability to degradation of pesticides and the use of these xenobiotic as carbon sources [19]. The destruction of herbicides in the environment occurs via participation by the soil, epiphytic and endophytic bacteria, particularly by the principle of co-metabolism.…”
Section: Herbicidesmentioning
confidence: 99%
“…Many researchers have noted an increase in the number of microorganisms under the influence of herbicides. Moreover, according to the literature a large number of bacteria, especially from Pseudomonas genus have the ability to degradation of pesticides and the use of these xenobiotic as carbon sources [19]. The destruction of herbicides in the environment occurs via participation by the soil, epiphytic and endophytic bacteria, particularly by the principle of co-metabolism.…”
Section: Herbicidesmentioning
confidence: 99%
“…However lesser availability of nitrogen, phosphorus and organic carbon in FA affects protein and amino acid metabolisms, disrupts energy flow in cells, growth and development as well as decrease resistance against plant diseases (Basu et al 2009;Yu et al 2013). At higher doses, FA can adversely affect soil biological properties (Kumar et al 2012;Nayak et al 2014). Several researchers (Pitchel and Hayes 1990;Garau et al 1991) reported that FA supplemented soil significantly reduced the microbial and enzymatic activities as well as process of N cycling such as nitrification and N mineralization.…”
Section: Introductionmentioning
confidence: 98%
“…[32] In the present study, there was a significant increase in MBC content with pendimethalin application initially after seven days of their respective application at all the three doses as compared to the untreated soil, that is, weedy check and hand-weeded control ( Table 2). This increasing trend of soil MBC continued till 30 days of application for HRE and RE and till 45 days for DRE but thereafter decreased gradually with time.…”
Section: Soil Mbcmentioning
confidence: 70%